Analyses of dynamic characteristics of functionally graded porous (FGP) sandwich plates with viscoelastic materials-filled square‐celled core. (1st December 2021) - Gao, Zhijiang; Li, Hui; Zhao, Jing; Guan, Jialin; Wang, Qingshan
Highlights: The FGP design shows good regulation on the structural resonance frequencies. The FGP-VSC sandwich plate shows high stiffness and high damping capacity. A stable performance increasing interval can be determined by the core size. The FGP-VSC sandwich plate shows better robustness to the boundary variations. Abstract: The dynamic characteristics of functionally graded porous (FGP) sandwich plates with viscoelastic material-filled square‐celled core (VSC) are investigated based on the constructed sandwich plate model. The dynamic model is built by combining the first-order shear deformation theory, the equivalent theory of material mechanics, the virtual spring technology, the modified Fourier-Ritz method, and the Newmark-Beta approach. Furthermore, the model validation is conducted, including the convergence study and the numerical validation under different geometrical parameters, material parameters, and boundary conditions. With the validated model, the parameter analysis is conducted to investigate the influence of the porous types, geometrical parameters, structure types, boundary conditions, and load types on the dynamic performance of the FGP-VSC sandwich plate.